Synthesis and characterization of silver nanoparticles mediated in glutathione and sodium alginate - Keshan Balavandy, Sepideh (2014)
Synthesis of silver nanoparticles (Ag NPs) has attracted huge interest from scientists due to its wide applications. Different pathways, such as physical and chemical reduction has been employed regarding the synthesis of Ag NPs. Many of them contain highly reactive chemicals and can cause potential environmental and biological risks. In comparison to those methods, green synthesis of nanoparticles using biopolymer provides a safe way of nanoparticle production with the size and shape of our interest. Nanoparticles formation depends on various factors such as metal ion concentration, pH, time and temperature as well as nature of reducing and stabilizing agent. There is a lack of a comprehensive study in optimizing important parameters for the green synthesis of Ag NPs in the biopolymer substrates. In this study, silver nanoparticles with the small size of 1 to 30 nm were successfully synthesized by green method in the substrate of sodium alginate (Na-Alg) and glutathione (GSH). Specific percentage of AgNO3 and biopolymeric substance were mixed together and stirred for different time at various temperature. Moreover, rapid synthesis of Ag NPs was achieved using an environmental friendly and biodegradable solvent that act as, stabilizing and reducing agent without use of high pressure or temperature, with the help of the accelerator. The silver nitrate, sodium alginate/glutathione, and sodium hydroxide were used as the silver precursor,stabilizer/ reducing agent and accelerator respectively. The crystalline structure of Ag NPs for all of the samples, the average size and size distributions, surface Plasmon resonance (SPR), surface morphology, and functional groups were studied using X-ray diffraction (XRD), transmission electron microscopy (TEM), UV-visible spectroscopy (UV-vis), scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) respectively. The XRD analysis confirmed that the crystallographic planes of the silver crystals were the face-centered cubic (fcc) types. The UV-visible absorption spectra showed the peaks characteristic of the surface plasmon resonance (SPR) bands of Ag NPs. The antibacterial activities of Ag NPs were investigated against Gram-negative and Gram-positive bacteria by the disk diffusion method using Mueller-Hinton Agar (MHA) that show highly antibacterial activity of Ag NPs. The properties of Ag/Na-Alg and Ag/GSH were studied as the function of time,temperature, concentration and pH until a relatively stable size and size distribution were achieved. The results from the UV-visible spectroscopy and TEM demonstrated that the initial concentration of 0.1 M for AgNO3 ,1.5 wt% for Na-Alg and GSH, in 90°C after 12h stirring time of reaction are the optimum for the synthesis of Ag Nps incorporate in Na-Alg and GSH. In addition, 5 ml is the optimum amount of sodium hydroxide (NaOH) for synthesis of Ag Nps in short time (30 minutes) of the reaction. From the results, all objective was achieved.